Subject Metaphors of Stars in Lithuanian and Russian Poetic Texts - Konickaja , Jelena; Jasiūnaitė , Birutė (Vilnius University Open Series, 2021)
The current article, that follows the research cycle analyzing natural phenomena metaphors, examines the star metaphors identified in the works of 40 Lithuanian and 54 Russian poets (mostly 20th century). It also studies the subject metaphors which constitute from the ethnolinguistic point of view the most numerous and most interesting group of six semantic subgroups of star metaphors. The subject metaphors of stars can be both substantive and verbal. However, the article focuses on substantive metaphors. They are divided into nine groups: 1) something written, drawn or embroidered (letters, written texts, books, drawings, figures); 2) lighting devices and other lighting means; 3) clothing, fabrics, yarn, knitted or woven items; 4) small metal, shiny, rounded or sharp objects (jewelry, coins, nails, needles, weapons, etc.); 5) buildings and their parts; 6) kitchen utensils; 7) food and drinks; 8) vehicles; 9) fragments of large objects and debris. The study showed the similarity of the poetic systems of the two languages, in which the same metaphorical models are presented, as well as their differences. The largest number of subject metaphors of stars in both poetic traditions was found in the first four groups, the examples from the following three groups were less common, while the examples in which star metaphors related to vehicles were hardly found. The differences between the two poetic systems may be observed due to the differences in cultures and traditional names of stars and constellations in the languages. The article noted that the author’s poetic metaphor in both Lithuanian and Russian could correlate with folklore tradition, that is with riddles, proverbs, legends and traditional beliefs, which are often common to the two languages.